Insights Into the Mechanism of Action of Chlorhexidine on Porphyromonas gingivalis - Karen Mejía; Adriana-Patricia Rodríguez-Hernández; Miryam Martínez-Hernández (International Journal of Dentistry)
Chlorhexidine (CHX) remains the most effective antiseptic in periodontal therapy, multiple reports have identified ultrastructural antibacterial effects of CHX on oral bacteria, however, little is known about its molecular mechanism of action on Porphyromonas gingivalis, an important pathobiont directly associated with the pathogenesis of periodontitis. A standardized suspension of P. gingivalis ATCC 33277 was expose to 0.20% CHX for 1 min, then counting colony forming units (CFUs) were recovered to determine the percentage of microbial inhibition. Protein extract integrity of the bacterial cells exposed to CHX was evaluated on a one-dimension sodium dodecyl sulfate polyacrylamide gel electrophoresis (1D SDS-PAGE) gel. The identification of the proteins expressed by P. gingivalis after its exposure to CHX was carried out by mass spectrometry (LC-MS). Exposure of P. gingivalis for 1 min to 0.20% CHX resulted in a 93% reduction in bacterial viability, in addition to an increase of 2.9-fold in protein expression, with the Lys gingipain protein showing the greatest increase. Exposure to 0.20% CHX 1 min on P. gingivalis resulted in 93% reduction in bacterial viability, in addition to inducing changes in the bacterial proteome, with an increased expression of gingipains, the main virulence factor of P. gingivalis.